Construction of an amylolytic Saccharomyces cerevisiae strain with high copies of α-amylase and glucoamylase genes integration for bioethanol production from sweet potato residue - Wang, Xin; Guo, Na; Hu, Jingting; Gou, Chenchen; Xie, Xinyue; Zheng, Haobo; Liao, Aimei; Huang, Jihong; Hui, Ming; Liu, Na (Frontiers in Microbiology, 2024)
Sweet potato residue (SPR) is the by-product of starch extraction from fresh sweet potatoes and is rich in carbohydrates, making it a suitable substrate for bioethanol production. An amylolytic industrial yeast strain with co-expressing α-amylase and glucoamylase genes would combine enzyme production, SPR hydrolysis, and glucose fermentation into a one-step process. This consolidated bioprocessing (CBP) shows great application potential in the economic production of bioethanol. In this study, a convenient heterologous gene integration method was developed. Eight copies of a Talaromyces emersonii α-amylase expression cassette and eight copies of a Saccharomycopsis fibuligera glucoamylase expression cassette were integrated into the genome of industrial diploid Saccharomyces cerevisiae strain 1974. The resulting recombinant strains exhibited clear transparent zones in the iodine starch plates, and SDS-PAGE analysis indicated that α-amylase and glucoamylase were secreted into the culture medium. Enzymatic activity analysis demonstrated that the optimal temperature for α-amylase and glucoamylase was 60–70°C, and the pH optima for α-amylase and glucoamylase was 4.0 and 5.0, respectively. Initially, soluble corn starch with a concentration of 100 g/L was initially used to evaluate the ethanol production capability of recombinant amylolytic S. cerevisiae strains. After 7 days of CBP fermentation, the α-amylase-expressing strain 1974-temA and the glucoamylase-expressing strain 1974-GA produced 33.03 and 28.37 g/L ethanol, respectively. However, the 1974-GA-temA strain, which expressed α-amylase and glucoamylase, produced 42.22 g/L ethanol, corresponding to 70.59% of the theoretical yield. Subsequently, fermentation was conducted using the amylolytic strain 1974-GA-temA without the addition of exogenous α-amylase and glucoamylase, which resulted in the production of 32.15 g/L ethanol with an ethanol yield of 0.30 g/g. The addition of 20% glucoamylase (60 U/g SPR) increased ethanol concentration to 50.55 g/L, corresponding to a theoretical yield of 93.23%, which was comparable to the ethanol production observed with the addition of 100% α-amylase and glucoamylase. The recombinant amylolytic strains constructed in this study will facilitate the advancement of CBP fermentation of SPR for the production of bioethanol.